(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Article on the practical use of nanomaterials, author Uktam Dekhkonovich Sherkulov, Republic of Uzbekistan, Navoi State Pedagogical Institute. The article provides information about the main nanotechnologies available in the world, their production and use in the national economy, problems of the application of nanotechnologies, and other information. The article is intended for scientific researchers and graduate students